La solennisation des fêtes dans la vie liturgique et temporelle des moines du Mont Saint-Michel (XIIIe-XVe siècles) - Louis Chevalier (Tabularia)
Analysis of the liturgical calendars, the ordinals and the ceremonial of Mont Saint-Michel, and particularly the degrees of solemnity, can inform us about the history of the cult of the saints and the liturgical and temporal life of the abbey. The degrees of solemnity, as markers of solemnization in the manuscripts, differentiate feasts according to their importance, indicating the number of lessons at the hour of matins and the candles lit in the choir, and mentioning the liturgical ornaments. Through a codicological and textual study of liturgical books in use between the thirteenth and fifteenth centuries at Mont Saint-Michel, this article examines the hierarchical categorisation of the feasts in the liturgy and the evolution of the degrees of solemnity on Mont Saint-Michel at the end of the Middle Ages, and the significance of the solemnization of a feast for the temporal life of the monks.